2020
DOI: 10.1007/s11606-020-05981-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Population Management for COVID-19 Patients

Abstract: BACKGROUND: Most patients infected with SARS-CoV-2 have mild to moderate symptoms manageable at home; however, up to 20% develop severe illness requiring additional support. Primary care practices performing population management can use these tools to remotely assess and manage COVID-19 patients and identify those needing additional medical support before becoming critically ill. AIM: We developed an innovative population management approach for managing COVID-19 patients remotely. SETTING: Development, imple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 4 publications
0
33
0
4
Order By: Relevance
“…Ours is one of a number of virtual care models that arose during the first months of the pandemic in the United States (Annis et al, 2020;Blazey-Martin et al, 2020;Sinha et al, 2020;Wosik et al, 2020 driven by physicians, residents or advanced practice clinicians, our approach relied more heavily on protocolised triage and follow-up by RNs. Another distinction is that our programme rarely used video telehealth despite the wide availability of a video telehealth infrastructure in VA.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is one of a number of virtual care models that arose during the first months of the pandemic in the United States (Annis et al, 2020;Blazey-Martin et al, 2020;Sinha et al, 2020;Wosik et al, 2020 driven by physicians, residents or advanced practice clinicians, our approach relied more heavily on protocolised triage and follow-up by RNs. Another distinction is that our programme rarely used video telehealth despite the wide availability of a video telehealth infrastructure in VA.…”
Section: Discussionmentioning
confidence: 99%
“…Population management strategies for COVID-19 have been proposed, but these are not specific for Paediatrics. 23 Paediatric primary care, both in hospital emergency departments and in the community, would benefit from clear testing criteria specific for children and adolescents that incorporate the considerations most relevant for these age groups. On developing these criteria, there are several important differences to adult populations that need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to mitigate the impact of COVID-19 on the community, healthcare provision and/or patient outcomes. Twenty-eight studies identified strategies to mitigate COVID-19's impact on communities, healthcare provision, and/or patient outcomes [19][20][21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43]45,[48][49][50]. These strategies were classified into the following subthemes: infection prevention and control measures, alternatives/modifications to traditional service delivery or workflow, government policy responses, and education.…”
Section: Cochrane Librarymentioning
confidence: 99%
“…Alternatives/modifications to traditional service delivery or workflow. Twenty-six studies identified alternatives/modifications to convential service delivery or workflow, which mitigated COVID-19 spread in communities, and reduced COVID-19's impact on healthcare provision and/or patient outcomes [19][20][21][22][23][24][25]7,28,30,[32][33][34][35][36][37][38][39][40][41][42][43]45,[48][49][50].…”
Section: Cochrane Librarymentioning
confidence: 99%
See 1 more Smart Citation